Formulating An Engineering Design Problem:A Structured Approach - Kaushik, M.; Baligar, Preethi; Joshi, Gopalkrishna (Journal of Engineering Education Transformations, 2018)
During recent times, several initiatives have been taken to redesign engineering curriculum to introduce students to the engineering design process starting from the freshman year itself. This involves taking these students from a world of exercise problem solving having single unique solution to the world of real wide engineering problem solving having multiple solutions. And it is observed to be a challenging task as the students are not familiar with ill-defined nature of engineering problems and are having a tendency to get stuck with the first solution that they get. Problem formulation is the first step in engineering design process in which students are expected to carve out problem definition for a given need statement. Students face difficulties in this step, in framing the problem statement and representing it in terms of functions, objectives and constraints depicting an engineering system.In this work, authors share their experience of mentoring freshman students in problem formulation phase of their course project which is done as part of a course, titled, "Engineering Exploration". The work is presented in terms of its evolution of the pedagogies and practices over three cycles of the delivery of the course. An inclusive pedagogy consisting of in-class, case-based reasoning and template based structured mentoring has resulted in improved quality of formulated problems. The paper discusses the details of processes and pedagogy.